2010
DOI: 10.1111/j.1600-0463.2009.02581.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of RNA amplification by multiplex RT‐PCR and IgM detection by indirect and capture ELISAs for the diagnosis of measles and rubella

Abstract: The aim of the study was to compare RNA amplification using multiplex RT-PCR and IgM detection by means of indirect and capture ELISAs for the diagnosis of measles and rubella. A total of 229 cases of maculopapular rash with serum and throat swab samples were included. Specific serological IgM to measles and rubella was determined by Enzygnost (Siemens) and Platelia (Bio-Rad). Both viruses were researched using multiplex RT-PCR performed on throat samples. Criteria for inclusion of measles or rubella cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…On the other hand, in samples collected more than 3 days after the appearance of the rash, more than 99% gave IgM‐positive results for CLIA and 98.5% gave for EIA (Table ). In agreement with our results, researchers in other studies found similar rates of false‐negative IgM results by Enzygnost in specimens collected during the first 3 days after onset of the rash, and a sensitivity approaching 100% in samples collected 3 days post rash onset . The lowest rate of false‐negative results in CLIA assay can be attributed to an antibody capture configuration; in fact, it has been stated in publications that capture EIA is more sensitive than indirect EIA, mainly in serum specimens taken too early with respect to symptoms after rash onset .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other hand, in samples collected more than 3 days after the appearance of the rash, more than 99% gave IgM‐positive results for CLIA and 98.5% gave for EIA (Table ). In agreement with our results, researchers in other studies found similar rates of false‐negative IgM results by Enzygnost in specimens collected during the first 3 days after onset of the rash, and a sensitivity approaching 100% in samples collected 3 days post rash onset . The lowest rate of false‐negative results in CLIA assay can be attributed to an antibody capture configuration; in fact, it has been stated in publications that capture EIA is more sensitive than indirect EIA, mainly in serum specimens taken too early with respect to symptoms after rash onset .…”
Section: Discussionsupporting
confidence: 92%
“…Specificity should prevail in diagnostic methods for surveillance of low‐incidence diseases, such as measles, in developed countries to ensure a good positive predictive value . The specificity of both LIAISON and EIA was excellent (97.9% and 96.8%, respectively) and similar to the values reported in other studies for Enzygnost EIA . Specificity results obtained in our study are particularly relevant considering that we included sera from patients with conditions reported to cause measles IgM false‐positive results .…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Establishment of the quantitative determination method allowed the further study of changes in RV IgM and CMV IgM titers in serum and the occurrence, development and prognosis of pathogen infection [29][30][31][32]. Compared with commercial CLIAs, the RV IgM and CMV IgM dual-TRFIA developed in the current study had a higher sensitivity and specificity, suitable for clinical applications.…”
Section: Discussionmentioning
confidence: 91%
“…1 Detection of measles virus (MeV) RNA by real-time RT-PCR (RT-rPCR) is a highly specific and sensitive rapid diagnostic tool to identify infection. [2][3][4][5] Despite a safe and effective vaccine available for over 50 years, MeV remains a serious public health threat worldwide. There are hurdles in the path to global measles elimination and the eventual eradication of the MeV.…”
Section: Introductionmentioning
confidence: 99%